2020
DOI: 10.1111/jvim.15899
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer and diffusion tensor imaging in dogs with intervertebral disk herniation

Abstract: Background: Quantitative magnetic resonance imaging (QMRI) techniques of magnetization transfer ratio (MTR) and diffusion tensor imaging (DTI) provide microstructural information about the spinal cord. Objective: Compare neurologic grades using the modified Frankel scale with MTR and DTI measurements in dogs with thoracolumbar intervertebral disk herniation (IVDH). Animals: Fifty-one dogs with thoracolumbar IVDH. Methods: Prospective cohort study. Quantitative MRI measurements of the spinal cord were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…It has been shown that FA will transiently increase with the presence of vasogenic edema 32 . In a previous study, FA was significantly lower in dogs with T2‐weighted intramedullary hyperintensity 7 . Therefore, the presence of vasogenic edema in combination with other pathologic processes (gliosis, inflammation, hemorrhage, or malacia) could negate the utility of FA in dogs with IVDH.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been shown that FA will transiently increase with the presence of vasogenic edema 32 . In a previous study, FA was significantly lower in dogs with T2‐weighted intramedullary hyperintensity 7 . Therefore, the presence of vasogenic edema in combination with other pathologic processes (gliosis, inflammation, hemorrhage, or malacia) could negate the utility of FA in dogs with IVDH.…”
Section: Discussionmentioning
confidence: 97%
“…First, the anatomic locations of spinal cord segments included in this study were variable. It is known that DTI values will vary between spinal cord segments 7 . This also applies to the age and weight variation between the dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many in vitro studies have shown that UTE-T1ρ enables the quantitative assessment of short T2 tissues in the musculoskeletal system, and UTE-T1ρ values increase with structural changes in short T2 tissues (14)(15)(16)(17)(18). The magnetization transfer ratio (MTR) provides a measure of the magnetization exchange rate of hydrogen protons bound to macromolecules such as collagen and free water (19). The UTE-MTR values have been used to evaluate the pools of protons indirectly by analyzing the interactions between the bound and pore water proton pools (20,21).…”
Section: Introductionmentioning
confidence: 99%